Respostas
respondido por:
6
I. h² = 3² + (3√3)²
h² = 9 + 9 · 3
h² = 9 + 27
h² = 36
h = √ 36
h = 6
II. w² = 6² + 2²
w² = 36 + 4
w² = 40
w = √40
w = 2 √10
III. 7² = (2√10)² + x²
49 = 4 · 10 + x²
49 = 40 + x²
x² = 9
x = √9
x = 3
h² = 9 + 9 · 3
h² = 9 + 27
h² = 36
h = √ 36
h = 6
II. w² = 6² + 2²
w² = 36 + 4
w² = 40
w = √40
w = 2 √10
III. 7² = (2√10)² + x²
49 = 4 · 10 + x²
49 = 40 + x²
x² = 9
x = √9
x = 3
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás